Strengthening Digital Literacy, Financial Management, and Special Skills to Face Human Resources Management Market Competition - Usmar Usmar; Sismiati Sismiati; Syarifuddin Sulaiman; Tamrin Lanori (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: In a rapidly changing labor market, three factors are essential: ownership of digital literacy, financial management skills, and specialized knowledge in increasing competitiveness in HR Management. These three factors are relevant to technological developments and market needs, so it is also essential for companies to implement the right strategy to achieve high competitiveness. Purpose: This paper aims to analyze digital literacy, financial management, and special skills in the context of human resources management market competition and simultaneously analyze all independent variables with the dependent variable. Design/methodology/approach: This research design uses a quantitative approach. The study population consisted of 158 managers of financial institutions in Bekasi, with a sample size of 158 managers selected. The respondents were selected through the random sampling method. The data analysis technique uses multiple linear regression analysis. Findings/Result: The research results show that the variables Digital Literacy, Financial Management, and Special Skills have a positive and significant effect on Human Resources Management Market Competition. Moreover, all independent variables have a significant effect on Human Resources Management Market Competition by 54.4%, while the remainder is influenced by other variables. Conclusion: Digital literacy, financial management, and special skills collectively form a powerful arsenal for HR professionals seeking to excel in the market. Originality/value (State of the art): This study contributes to the limited empirical literature by quantitatively assessing the combined impact of digital literacy, financial management, and special skills on HR market competitiveness, offering practical insights for HR strategy development in the context of emerging market economies. Keywords: digital literacy, financial management, special skills, human resources management, market competition